Climatic and endothermic thermal stress adaptation may be a major driver of emerging and emergent multidrug resistant fungi - Ibe, Chibuike; Pohl, Carolina Henritta (Frontiers in Microbiology, 2025)
BackgroundThe impact of climate change and increasing global temperature is contributing to the emergence of unknown and the reemergence of known fungal pathogens.Main bodyIn the process of adapting to the increasing global temperatures, some fungi have evolved multidrug resistance traits thus narrowing the therapeutic options in our antifungal arsenal. Interestingly, all emerging fungal pathogens and known emergent fungi are multidrug and pandrug resistant, suggesting that the drug resistance traits observed are partly due to thermal stress-induced cross stress-responses. This paper argues that the acquired drug resistance traits may also be driving increased virulence and adaptation to infection-related conditions, resulting in the outbreak of community and hospital infections.ConclusionContinued surveillance and more research are required to enhance our understanding of the impact of heat-induced evolution of antifungal resistance in this rapidly evolving area of research that may define a new era in medical mycology.